2002
DOI: 10.1093/nar/gkf410
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of a novel mismatch repair activity in a bladder tumor cell line

Abstract: We demonstrate here that a cell line derived from a bladder cancer is defective in strand-specific mismatch repair. The mismatch repair deficiency in this cell line is associated with microsatellite instability and blocks an early step in the repair pathway. Since the addition of a known mismatch repair component hMutSalpha, hMutSbeta, hMutLalpha, replication protein A or proliferating cellular nuclear antigen could not restore mismatch repair to the mutant extract, the bladder tumor cell line is likely to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…These results suggest that the hMSH2(M688R)-hMSH6 protein can functionally inhibit the WT hMSH2-hMSH6 during the mismatch excision process. Similar mixing studies with the hMSH2(M688I)-hMSH6 protein suggest a modest inhibition of excision (data not shown) The complete MMR reaction was examined using a cellular extract deficient for hMSH2 (N6 cells) (44). In these studies, nick-directed MMR results in the reconstitution of a restriction endonuclease site (35).…”
Section: The Hmsh2(m688r)-hmsh6 Interferes With Wt Hmsh2-hmsh6 During Mmrmentioning
confidence: 79%
“…These results suggest that the hMSH2(M688R)-hMSH6 protein can functionally inhibit the WT hMSH2-hMSH6 during the mismatch excision process. Similar mixing studies with the hMSH2(M688I)-hMSH6 protein suggest a modest inhibition of excision (data not shown) The complete MMR reaction was examined using a cellular extract deficient for hMSH2 (N6 cells) (44). In these studies, nick-directed MMR results in the reconstitution of a restriction endonuclease site (35).…”
Section: The Hmsh2(m688r)-hmsh6 Interferes With Wt Hmsh2-hmsh6 During Mmrmentioning
confidence: 79%
“…These include endometrial, ovarian, gastric, cervical, breast, skin, lung, prostate, and bladder tumors as well as glioma, leukemia, and lymphoma. Biochemical studies confirmed that MSI cell lines from sporadic leukemia, endometrial, ovarian, prostate, and bladder cancers are defective in strand-specific MMR [32,125,126]. Interestingly, MSI in sporadic non-colonic tumors is often associated with hypermethylation of the promoter of hMLH1 (see below for details), and few mutations in MMR genes have been identified in these cells.…”
Section: Mmr Defects In Hereditary Non-polyposis Colorectal Cancer (Hmentioning
confidence: 89%
“…Hypermethylation of the hMLH1 promoter has been demonstrated in sporadic endometrial, gastric, and breast cancers (175,(194)(195)(196). Biochemical studies have shown that cell lines derived from sporadic endometrial, ovarian, prostate, and bladder cancers are defective in strandspecific MMR (53,144,145,197,198). These findings suggest that MMR defects are a likely cause of non-colonic sporadic cancer with MSI, although other mechanisms may also be involved in causing the MSI mutator phenotype.…”
Section: Mmr Deficiency In Sporadic Non-colorectal Cancermentioning
confidence: 99%